1997
DOI: 10.1366/0003702971940765
|View full text |Cite
|
Sign up to set email alerts
|

In situ Spectroscopy of Polymers Subjected to Supercritical CO2: Plasticization and Dye Impregnation

Abstract: In situ FT-IR spectroscopy has been used to study poly(methyl methacrylate) films subjected to high-pressure and supercritical CO2. Spectral changes indicate increased molecular mobility of ester groups due to the plasticization effect of CO2 on PMMA. This increase in PMMA segmental mobility has been used to impregnate Disperse Red 1 dye (DR1) into polymer film from a supercritical fluid solution. The enhanced diffusion process was observed in situ via FT-IR and UV/vis spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 27 publications
0
90
0
3
Order By: Relevance
“…PLA, as other polyesters, is known to establish low energy interactions (of Lewis acid-base nature) between CO 2 molecules (electron acceptor) and carbonyl groups of the polymer (electron donor), which leads to plasticization and swelling [22,[34][35][36]. As a result, PLA chains are becoming more spaced, PLA intermolecular interactions reduce, the system mobility increases and new sorption sites are exposed, favoring therefore CO 2 sorption [22,33,37]. The CO 2 sorption isotherm of PET was also determined using the same gravimetric technique (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…PLA, as other polyesters, is known to establish low energy interactions (of Lewis acid-base nature) between CO 2 molecules (electron acceptor) and carbonyl groups of the polymer (electron donor), which leads to plasticization and swelling [22,[34][35][36]. As a result, PLA chains are becoming more spaced, PLA intermolecular interactions reduce, the system mobility increases and new sorption sites are exposed, favoring therefore CO 2 sorption [22,33,37]. The CO 2 sorption isotherm of PET was also determined using the same gravimetric technique (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the polycarbonate and PMMA with carbonyl (C=O) have the maximum affinity for carbon dioxide and the most obvious plasticity. Kazarian used FTIR and ATR infrared spectrum analysis results [31,32] to prove that the oxygen atom of carbon dioxide has polar effect on polymer carbonyl. The carbon dioxide was equivalent to the Lewis Pair reacted electron acceptor (acid); thus, using carbon dioxide as dissolvent is very potential in polymer dyeing.…”
Section: Evolution Of Supercritical Fluid Dyeingmentioning
confidence: 99%
“…In 1996, Kazarian et al used infrared spectrometer FTIR and AT R and supercritical dyeing equipment with window to observe the plasticity of supercritical carbon dioxide on different polymer membranes [31,32], thus initiating the direct application of instrumental analysis. In 2005, Kazarian [72] used Raman infrared spectrometer to observe the diffusion behavior of C.I.…”
Section: Application Of Instrumental Techniquementioning
confidence: 99%
“…Traditional mid-IR (MIR) spectroscopy has proven its usefulness for quantifying solute concentrations in the polymer and fluid [21][22][23] and has, in fact, been applied to measure the solubility and sorption of CO 2 in polymers at pressures below 5 atm. 24,25 In addition to measurement of concentrations, traditional MIR spectroscopy is a valuable tool for studying the effects of the dissolved fluid on the polymer 23,26,27 and specific interactions of CO 2 with polymers. 28 The ability to gain molecular level insight, and, thus, a molecular basis for understanding macroscopic phenomena such as gas solubilities, is a major advantage of IR spectroscopy over other techniques.…”
Section: In Situ Ftir Spectroscopymentioning
confidence: 99%